2003
DOI: 10.1590/s0100-204x2003001000009
|View full text |Cite
|
Sign up to set email alerts
|

Frações de fósforo em Latossolos

Abstract: Resumo -O objetivo deste trabalho foi verificar se o histórico de uso, adubação fosfatada, inoculação micorrízica e cultivo com braquiária e soja, em casa de vegetação, alteram as frações de P em três Latossolos. Foi determinado o P ligado a Al (P-Al), Fe (P-Fe) e Ca (P-Ca) e as frações de P separadas com resina, NaHCO 3 , NaOH, HCl e digestão com H 2 SO 4 e H 2 O 2 . As frações orgânicas e inorgânicas foram separadas por autoclavagem. No Latossolo Amarelo coeso (LAx) e Latossolo Vermelho ácrico (LVw), o P-Al,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 20 publications
1
8
0
2
Order By: Relevance
“…These results demonstrate the efficiency of the forages in providing these nutrients to the soil. Soils with Palisade grass had higher P levels in the labile fractions, increasing the absorption of this nutrient by plants (Silva et al, 2003). The OM in NTS also reduces the contact between soil colloids and the phosphate ion, reducing adsorption reactions, while residue decomposition (Figure 3) releases and redistributes organic, more mobile P forms that are less susceptible to adsorption reactions in the soil (Mesquita Filho and Torrent, 1993).…”
Section: Resultsmentioning
confidence: 99%
“…These results demonstrate the efficiency of the forages in providing these nutrients to the soil. Soils with Palisade grass had higher P levels in the labile fractions, increasing the absorption of this nutrient by plants (Silva et al, 2003). The OM in NTS also reduces the contact between soil colloids and the phosphate ion, reducing adsorption reactions, while residue decomposition (Figure 3) releases and redistributes organic, more mobile P forms that are less susceptible to adsorption reactions in the soil (Mesquita Filho and Torrent, 1993).…”
Section: Resultsmentioning
confidence: 99%
“…The fractionation of P is a tool of characterization of the nutrient in the soil, based on the availability to plants in the short and long term, which determines the P compartments with different chemical stability degrees (Silva et al, 2003). Furthermore, the distinction of P fractions plays an important role in the prediction of the soil P behavior, and in associations of P with routine extractors it makes a better understanding of the P dynamics and plant availability possible.…”
Section: Introductionmentioning
confidence: 99%
“…In pot experiments, plant roots are so densely distributed that nearly all soil in the pots are close to the rhizosphere, where pH is usually lower, and P availability may be higher. This may explain the effect observed by Silva et al (2003).…”
Section: Resultsmentioning
confidence: 65%
“…Gatiboni et al (2007) observed no changes in soil-P fractions as affected by fertilization, whereas Silva et al (2003) observed significant decreases in Fe/Al-P after growing Urochloa sp. in a pot experiment, due to high P uptake by grass.…”
Section: Resultsmentioning
confidence: 86%